The Irony of Fishermen’s Condition in Makassar City (The Tiplogy Analysis Based on Laws Number 45 Years 2009) - Umiyati Haris (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
This research purposed to describe condition of fisherman in Makassar City and analyze factors that caused those fisherman are marginalized and related with the policy of laws, specifically the laws Number 45 Years 2009 about fishery. The writing techniques of this research use qualitative-descriptive with lots of data are obtained from direct interview result and observation. The interviewee determination technique using purposive sampling in three places, they are PT.Pelindo IV Makassar; Pasar Lelong; and Nelayan Village. The result of research indicates that fisherman societies in Makassar City are divided by traditional fisherman and modern fisherman. Moreover, the factor which affected traditional fisherman becomes marginalized is related with the Laws Number 45 Years 2009 and some articles are not synchronized with the reality. Key words: Traditional Fisherman, Modern Fisherman, policy, Laws Number 45 Years 2009